122k views
4 votes
Find all solutions to x³+3x² − 9x − 27 = 0 by factoring the equation.

User Tested
by
6.0k points

1 Answer

5 votes

Answer:

The solutions are
x=-3,\:x=3

Explanation:

To factor this cubic polynomial
x^3+3x^2-9x-27 you must:

  • Group the polynomial into two sections


x^3+3x^2-9x-27=\left(x^3+3x^2\right)+\left(-9x-27\right)

  • Factor out -9 from
    (-9x-27)


(-9x-27)=-9\left(x+3\right)

  • Factor out
    x^2 from
    (x^3+3x^2)


(x^3+3x^2)=x^2\left(x+3\right)


x^3+3x^2-9x-27=-9\left(x+3\right)+x^2\left(x+3\right)

  • Factor out common term
    x+3


-9\left(x+3\right)+x^2\left(x+3\right)=\left(x+3\right)\left(x^2-9\right)


x^3+3x^2-9x-27=\left(x+3\right)\left(x^2-9\right)

  • Factor
    x^2-9


x^2-9=\left(x+3\right)\left(x-3\right)


x^3+3x^2-9x-27= \left(x+3\right)\left(x+3\right)\left(x-3\right)


x^3+3x^2-9x-27=\left(x+3\right)^2\left(x-3\right)=0

  • Using the Zero Factor Theorem: = 0 if and only if = 0 or = 0


x+3=0, \quad{x=-3}\\x-3=0, \quad{x=3}

The solutions are


x=-3,\:x=3

User Boisterouslobster
by
5.7k points